Enhancing Arabic Vocabulary Learning Outcomes through ‎‎Cooperative Learning Model STAD with Video Media Assistance - Intan Rokmana; Muhammad Akmansyah; Erlina Erlina; Koderi Koderi; Muhammad Sufian (Universitas Muhammadiyah Gorontalo, 2025)
This research aims to investigate the planning, implementation, and ‎improvement of Arabic Vocabulary Learning Outcomes through the ‎cooperative learning model of Student Teams Achievement ‎Divisions (STAD) with the assistance of video media for eighth-‎grade students at Junior High School Manzilul Barakah in ‎Pagaralam City. This type of research is classroom action research. ‎Classroom action research is a process undertaken by individuals or ‎groups desiring change in a particular situation, involving planning, ‎implementing, and reflecting, which is expected to solve the ‎encountered problems. The results of the research show that the ‎planning and implementation of learning using the Cooperative ‎Learning model of Student Teams Achievement Divisions (STAD) ‎with the assistance of video media at Manzilul Barakah junior high ‎school show a significant increase in Arabic vocabulary learning ‎outcomes. From the pre-cycle with a completeness of 50%, cycle I ‎increased to 70%, and cycle II reached 80%, showing an average ‎increase of 30%. This method successfully enhances students' ‎understanding, motivation, and cooperation, proving that the ‎integration of technology and well-planned and continuously ‎evaluated cooperative learning methods can improve learning ‎effectiveness.‎